Measurement of elastic modulus change due to stress state in thin samples by using laser ultrasound technique
Chapter 1 Introduction; Chapter 2 Literature review; Chapter 3 Methodology; ... In this study, we obtained the change of elastic modulus due to stress state for thin samples. The material properties were determined by using the Laser ultrasound techniques (LUT), particle swarm optimization (PSO) algorithm and an inversion program. The inversion program uses Lamb wave dispersion curve from theory and experiment to invert and get the material properties includes elastic modulus, thickness and Poison’s ratio. The material properties changes when stress state or residual stress changes. Hence, we can measure stress state or residual stress in thin samples by this technique.